The future of direct response fundraising - Warwick, Mal (Henry Stewart Talks, 2009)
Broad potential of direct marketing for nonprofit organizations, Evolution of techniques and new media employed, Principal characteristics of nonprofit direct marketing, Multichannel integration is the key to the future use of direct marketing in nonprofit organizations, Current trends and future prospects